ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK PEMERINTAH DAN BANK SWASTA MENGGUNAKAN METODE CAMEL - Tiarso, Ernissa Nandiati; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTBanking industry has experienced many changes in the last years. This industry has become morecompetitive becauseof variousregulationswhich have been set by Bank of Indonesia. State Commercial Banks andPrivate CommercialBanks haveexperienced tight competition in order to attract customers whose desiresinhaving banking services are always changes. This research is aimed to find out the comparison the financialperformance between state commercial banks which are owned by the government and private commercialBankswhich are owned by private owners in Indonesia by using CAMEL method (Capital, Asset, Management,Earnings, Liquidity). This research is quantitative research and it has been done by using comparing average oftwo paired samplesmethod from two independent population. The samples have been selected by using purposivesampling. The analysis technique has been carried out by using independent sample t-test for the data which isnormally distributed whereas the data which is not normally distributed is done by usingmann-whitney.Theresult of this research shows that NPL, NPM and ROA have been proven that there are no significant differentbetween the financial performance of Bankswhich are owned by Government and Bankswhich are owned byprivates, meanwhile ratio CAR, BOPO and LDR are proven that there aresignificant different between financialperformance Banks which are owned by the Government and Banks which are owned by privates.Keywords:State commercial bank, private commercial bank, bank financial performance, financial ratio,CAMEL.